The Effect of Katuk Leaf Supplementation in the Ration on the Number of Erythrocytes and Hemoglobin Value in Rex Rabbits - Imam Satiyana; Mohandas Indradji; Ning Irianti (Program Studi Peternakan, Fakultas Pertanian, Universitas Veteran Bangun Nusantara, 2021)
Increased productivity of rabbits was through improved feed. Katuk plant has high nutritional value and its leaves contain nutrients needed by the body. The protein content in feed greatly affects the character of the blood. The purpose of this study was to optimize the effect of using katuk leaf supplementation on the number of erythrocytes and the hemoglobin value of rex rabbits. The research material were 18 rex rabbits, basal feed added with katuk leaves. The research method used was Completely Randomized Design (CRD) with three treatments, each treatment repeated six times, so that there were 18 experimental units. The treatments were R0: basal diet without katuk leaf supplementation, R1: basal diet with 5% katuk leaf supplementation, R2: basal diet with 10% katuk leaf supplementation. The variables measured were the number of erythrocytes and the value of hemoglobin. Data were analyzed using analysis of covariance (ANCOVA). The results showed that rabbit rex erythrocytes were R0 = 4.7 ± 0.39 x 106/µL; R1 = 4.99 ± 0.28 x 106/µL; R2 = 4.76 ± 0.31 x 106/µ. The average result of the three treatments above was 4.83 ± 0.83 x 106/µL. The erythrocyte mean results were still in the normal range. The results of the analysis of variance showed that the three treatments did not show significant differences. The conclusion of the study was that katuk leaf supplementation can be given to rabbit rex up to a level of 10% without affecting the physiological process of livestock in terms of the number of erythrocytes and hemoglobin values which are relatively the same.Key words : erythrocytes, hemoglobin, katuk leaves, rabbit rex.